Measures of Restrictions on Inward Foreign Direct Investment for OECD Countries - Golub, Stephen S.. (OECD Publishing, 2003)
This paper provides new measures of restrictions on inward foreign direct investment (FDI) for OECD countries. Several different types of restrictions are considered: limitations on foreign ownership, screening or notification procedures, and management and operational restrictions. These restrictions are computed for nine sectors and eleven sub-sectors, most of which are in services, and then aggregated into a single measure for the economy as a whole. According to the aggregate indicators, the last two decades, and especially the 1990s, have witnessed dramatic liberalisation in FDI restrictions. OECD countries are now generally open to inward FDI, although there remain substantial differences between countries and across industries. The most open countries are now in Europe, at least as far as statutory restrictions are concerned. The preponderance of remaining restrictions is in services, with almost no overt restrictions in manufacturing...